Islamic Approach Towards Resolving Religious Disputes among Semitic Religious Followers in Northern Nigeria - Muhammad Suleiman; Mariyah Muhammad Shafiu (CV Media Inti Teknologi, 2025)
The study aims to examine the Islamic approach to tribal differences concerning the tribal crisis in northern Nigeria, also to deliberate on the significance of discarding tribal differences to unity based on Shari’ah guidance as related to the north of Nigeria, and to assess the implications and challenges of upholding tribal differences as a basis of disunity in northern Nigeria. This study utilizes a qualitative descriptive design to deeply analyze the Islamic approach to conflict resolution, focusing on religious disputes among Semitic religious followers in Northern Nigeria. The design will allow for an understanding of cultural, social, and religious factors influencing tribal conflicts and religious disputes. The results of this study indicate that Islamic teachings have great potential in easing religious and ethnic conflicts in Northern Nigeria, which are often triggered by tensions between tribes and religions. Islam teaches principles of peace that are not only theological but also practical in everyday life, such as respect for individual rights and the importance of brotherhood (ukhuwah). this study also found that tolerance is one of the most emphasized values in Islamic teachings. This tolerance is reflected in the behavior of the Prophet Muhammad (PBUH) who showed respect for other religions, such as in the Medina Charter which gave full rights to non-Muslim groups to practice their beliefs without coercion. The study concludes that to achieve sustainable peace, the people of Northern Nigeria must implement Islamic teachings that emphasize social justice, equality, and respect for individual rights.